Konsep Pendidikan Profetik sebagai Pilar Humanisasi - Yuni Masrifatin (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2019)
Prophetic education can be understood as a set of theories that not only describe and transform social phenomena, and not only change things for the sake of change, but more than that, are expected to direct changes on the basis of ethical and prophetic ideals. The three main pillars in prophetic social science are: amar ma'ruf (humanization), nahi munkar (liberation), and tu`minuna blades (transcendence). The existing education process tends to be monotonous, indoctrinative, teacher-centered, top-down, mechanical, verbal, cognitive and the mission of education has been misleading. No wonder there is an impression that Islamic education practices and processes are sterile from the context of reality, so that they are not able to make a clear contribution to the various problems that arise. Education, especially religion, is considered not effective enough to contribute in solving problems. Because of this, many ideas emerged about the need to interpret and reorient, including making a paradigm shift from the current educational practice. Education must be interpreted as an effort to help humans reach their reality by optimizing all their human potential. With this understanding, all processes leading to the realization of human potential optimization, regardless of place and time, are categorized as educational activities. Conversely, if there is a practice that is said to be education it actually hinders development, the potential for humanity in its various forms, then this is actually not the practice of education. However, it must be realized that there are indeed differences in methods or strategies between one another, but these differences should only be limited to the technical implementation, not the meaning of education itself.